Activation of the Amino Acid Response Pathway Blunts the Effects of Cardiac Stress. Issue 5 (May 2017) - Qin, Pu; Arabacilar, Pelin; Bernard, Roberta E.; Bao, Weike; Olzinski, Alan R.; Guo, Yuanjun; Lal, Hind; Eisennagel, Stephen H.; Platchek, Michael C.; Xie, Wensheng; del Rosario, Julius; Nayal, Mohamad; et al.
Abstract : Background: The amino acid response (AAR) is an evolutionarily conserved protective mechanism activated by amino acid deficiency through a key kinase, general control nonderepressible 2. In addition to mobilizing amino acids, the AAR broadly affects gene and protein expression in a variety of pathways and elicits antifibrotic, autophagic, and anti‐inflammatory activities. However, little is known regarding its role in cardiac stress. Our aim was to investigate the effects of halofuginone, a prolyl‐tRNA synthetase inhibitor, on the AAR pathway in cardiac fibroblasts, cardiomyocytes, and in mouse models of cardiac stress and failure. Methods and Results: Consistent with its ability to inhibit prolyl‐tRNA synthetase, halofuginone elicited a general control nonderepressible 2–dependent activation of the AAR pathway in cardiac fibroblasts as evidenced by activation of known AAR target genes, broad regulation of the transcriptome and proteome, and reversal byl ‐proline supplementation. Halofuginone was examined in 3 mouse models of cardiac stress: angiotensin II/phenylephrine, transverse aortic constriction, and acute ischemia reperfusion injury. It activated the AAR pathway in the heart, improved survival, pulmonary congestion, left ventricle remodeling/fibrosis, and left ventricular function, and rescued ischemic myocardium. In human cardiac fibroblasts, halofuginone profoundly reduced collagen deposition in a general control nonderepressible 2–dependent manner and suppressed the extracellular matrix proteome. In human induced pluripotent stem cell–derived cardiomyocytes, halofuginone blocked gene expression associated with endothelin‐1‐mediated activation of pathologic hypertrophy and restored autophagy in a general control nonderepressible 2/eIF2α‐dependent manner. Conclusions: Halofuginone activated the AAR pathway in the heart and attenuated the structural and functional effects of cardiac stress.